Larva of Glyptotendipes (Glyptotendipes) glaucus (Meigen 1818) (Chironomidae, Diptera)—morphology by Scanning Electron Microscope (SEM), karyotype, and biology in laboratory conditions - Kownacki, Andrzej; Woznicka, Olga; Szarek-Gwiazda, Ewa; Michailova, Paraskeva (Zootaxa, 2016)
Larvae belonging to the family Chironomidae are difficult to identify. The aim of the present study was to describe the larval morphology of G. (G.) glaucus with the aid of a Scanning Electron Microscope (SEM), the karyotype and biology based on materials obtained from laboratory culture. Describing the morphology of larvae, special attention was paid to rarely or never described structures like the maxilla (lacinia and maxillary palp), the long plate situated below the ventromental plate, and plate X situated between lacinia and mentum. The use of SEM allowed also to obtain better images of labrum and ventromental plate. Morphological features of this species have been supplemented by karyotype and biology of larvae in laboratory conditions. Under controlled experimental conditions we found non-synchronous development of G. (G.) glaucus larvae hatched from one egg mass reflected in different lengths of larvae and emerged imagoes.